Sistem Pengendali Mesin Solar Cells Automatic Tabber Stringer pada Penyolderan String di PT. Indonesia Solar Global - Fina Ayu Lestari; Bagus Dwi Cahyono (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
In the production of photovoltaic modules, solar cells are an input that is processed to produce a photovoltaic module output. The core process of making photovoltaic modules is at the soldering stage of solar cells until the solar cells are assembled in series and become a string. The soldering process at PT. Indonesia Solar Global is done automatically using a machine called Solar Cells Automatic Tabber Stringer. This soldering machine uses the infrared soldering method in which the light produced from infrared produces heat energy so that it can solder the solar cells. So that in the soldering process using this machine an analysis is carried out to be able to classify what type of control system is on the Solar Cells Automatic Tabber Stringer machine. This research was conducted using data collection by means of interviews and direct observation in the field. This research produces new knowledge related to the type of control system that exists in the Solar Cells Automatic Tabber Stringer machine which is capable of soldering solar cells to produce a string output.